2019
DOI: 10.1364/boe.10.001339
|View full text |Cite
|
Sign up to set email alerts
|

Digital staining through the application of deep neural networks to multi-modal multi-photon microscopy

Abstract: Deep neural networks have been used to map multi-modal, multi-photon microscopy measurements of a label-free tissue sample to its corresponding histologically stained brightfield microscope colour image. It is shown that the extra structural and functional contrasts provided by using two source modes, namely two-photon excitation microscopy and fluorescence lifetime imaging, result in a more faithful reconstruction of the target haematoxylin and eosin stained mode. This modal mapping procedure can aid histopat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 33 publications
0
55
0
Order By: Relevance
“…Recently, deep learning has been demonstrated to be an effective virtual staining method. The success of this virtual staining has been illustrated using several different microscopy modalities as input images [49], [51], [126], [127]. Rivenson et al [49] demonstrated the efficacy of the deep learning-based staining using images of a single autofluorescence channel of an unstained tissue and that the technique can be applied to several different tissue types and stains (Masson's Trichrome and Jones stain in addition to the standard H&E).…”
Section: I N S I L I C O L a B E L I N G U S I N G D E E P L E A mentioning
confidence: 99%
“…Recently, deep learning has been demonstrated to be an effective virtual staining method. The success of this virtual staining has been illustrated using several different microscopy modalities as input images [49], [51], [126], [127]. Rivenson et al [49] demonstrated the efficacy of the deep learning-based staining using images of a single autofluorescence channel of an unstained tissue and that the technique can be applied to several different tissue types and stains (Masson's Trichrome and Jones stain in addition to the standard H&E).…”
Section: I N S I L I C O L a B E L I N G U S I N G D E E P L E A mentioning
confidence: 99%
“…Image registration is the process of bringing in the same system of coordinates, and geometrically aligning, two or more images of the same scene, which may be taken at different times, under different acquisition conditions, or by different sensors 35 . In microscopy imaging, multimodal and/or monomodal registration are typically required to perform side-by-side image comparison, which is often needed to monitor morphological changes and motion, or to perform template-, or atlas-based segmentation, classification, detection, etc [36][37][38][39][40][41] . Furthermore, monomodal registration, e.g.…”
Section: Utilitymentioning
confidence: 99%
“…A growing collection of studies have used GANs to synthetically stain images of histological tissue sections, which can save institutions time and money (both in reagents and technologists' time) (Bayramoglu et al, 2017;Borhani et al, 2019;De Biase, 2019;Lahiani et al, 2018;Quiros et al, 2019;Rana et al, 2018;Rivenson, Liu, et al, 2019;Rivenson, Wang, et al, 2019;Xu et al, 2019). GAN models have also been used to remove artificial and natural discolorations in images of stained histological tissue sections, removing artifacts that could perturb deep learning analyses (Bentaieb & Hamarneh, 2018;Ghazvinian Zanjani et al, 2018;Pontalba et al, 2019).…”
Section: Introductionmentioning
confidence: 99%